Pengaruh Kepemimpinan, Disiplin, dan Motivasi terhadap Kinerja Karyawan LPD Kedonganan - Ni Nyoman Yanti Anjastari; A. A. Ngr. Oka Suryadinatha Gorda (Studi Ilmu Manajemen dan Organisasi, 2025)
Purpose: This study aimed to examine the influence of transformational leadership, work discipline, and motivation on employee performance at LPD Kedonganan Traditional Village. The objective of this study was to determine how these factors affect productivity and performance outcomes. Methodology: A mixed-method approach was applied, primarily quantitative, using data collected from 60 respondents through structured interviews. Data analysis employed the SmartPLS4 statistical tool with the Structural Equation Modeling (SEM-PLS) technique to test the proposed hypotheses. Results: The findings show that transformational leadership, work discipline, and motivation significantly and positively impact employee performance. Transformational leadership improves performance quality, strong discipline boosts productivity, and motivation enhances employee effectiveness. Conclusion: The study concludes that LPD Kedonganan should strengthen leadership practices, enforce better discipline, and improve motivational efforts to enhance overall employee performance. Limitations: This study is limited to three variables—transformational leadership, discipline, and motivation—excluding other influential factors such as organizational culture or compensation. The quantitative design also restricts the depth of insight into employees’ perceptions. Contribution: This study provides strategic input for LPD Kedonganan and similar institutions to improve management practices. It also serves as a basis for future research by recommending the inclusion of additional variables such as job satisfaction and work environment, and encouraging comparative studies across different local credit institutions.